A QoS awareness scheme sustaining seamless handover for network mobility - Loay F. Hussein, Loay F.; Hassan Abdalla Hashim, Aisha; Habaebi, Mohamed Hadi; Hassan, Wan Haslinah (Indian Society for Education and Environment & Informatics Publishing Limited, 2016)
Objectives: This article proposes a new scheme known as (Diff-FH NEMO) to enhance seamless handover for the users within network mobility. Methods/Analysis: The proposed scheme adapts the method of Fast Hierarchical Mobile IPv6 (FHMIPv6) to shrink binding locality signaling issues. Furthermore, it exploits DiffServ depiction to pull off silky delivery of real time trafficking in heterogeneous network mobility. Network Simulator (NS-2) tool version 2.28 and analytical analysis are utilized to implement and assess the performance of the proposed scheme. Findings: Network Mobility (NEMO) basic support protocol (RFC 3963) endorsed by Internet Engineering Task Force (IETF) to enlarge the maneuver of Mobile IPv6 for better unremitting Internet connectivity to the users of mobile network. Here the protocol swaps mobility task function from mobile nodes to NEMO’ router. In mobility network the router is identified as Mobile Router (MR), which executes location update with its Home Agent (HA) to launch a bi-directional tunnel between the HA and MR. NEMO is premeditated with explication so that network mobility is transparent to the nodes in order to ease location update signaling that could happen by each Mobile Network Node (MNN). Yet, delays in data delivery and higher overheads